High-dose melphalan-based chemotherapy and autologous stem-cell transplantation for high-risk osteosarcoma in children: A single-institute experience and review of the literature - Hideki Sakiyama; Satoru Hamada; Nobuyuki Hyakuna; Takeshi Yagi; Tokiko Oshiro; Taichi Uehara; Shinobu Kiyuna; Jiro Miyamoto; Takehiro Matsuda; Takeshi Higa; Koichi Nakanishi (Elsevier, 2021)
Background: The prognosis of high-risk osteosarcoma, defined by the presence of chemo-resistance, metastatic disease at diagnosis, and relapse, remains poor. The efficacy of high-dose chemotherapy (HDC) and autologous stem-cell transplantation (ASCT) for high-risk osteosarcoma is still unclear. Methods: We retrospectively reviewed pediatric patients with high-risk osteosarcoma who underwent HDC and ASCT at our institution between 2002 and 2018 and performed a review of the literature regarding the efficacy of HDC and ASCT for high-risk osteosarcoma. Results: Six patients with high-risk osteosarcoma underwent high-dose melphalan (180 mg/m2)-based chemotherapy followed by ASCT. Two patients received HDC consisting of ifosfamide and melphalan. Three patients received HDC consisting of etoposide, carboplatin, and melphalan. One patient underwent tandem HDC consisting of thiotepa and etoposide followed by melphalan, thiotepa, and etoposide. Non-hematological toxicities presented mainly as mucositis and diarrhea. Two patients developed grade 3 mucositis. No life-threatening toxicities were observed in any of the six patients. One patient with disease progression before HDC died of multiple metastases, while five patients, with no evidence of disease in the peri-transplant periods, were alive at the time of publication; there was no disease recurrence at a median follow-up period of 144 months (range, 24-215 months). Our review of the literature supports the use of HDC with a higher dose of melphalan (180-280 mg/m2) for high-risk osteosarcoma. Conclusions: Melphalan-based HDC and ASCT can be a promising treatment for high-risk osteosarcoma. Additionally, surgical removal of macroscopic residual lesions may be essential in peri-transplant periods.